Politik Identitas Budaya Pada Pemerintahan Daerah:: Peran Pendidikan Berbasis Marga Suku Batak Dalam Membangun Ketahanan Politik Dan Budaya - Muhammad Salisul Khakim (Institut Pemerintahan Dalam Negeri, 2025)
The cultural identity of the Batak people can be clearly seen in their clan names, but those related to the distinctive Batak people's personal names are starting to fade, replaced by modern names. The declining existence of local identity also has an impact on the declining resilience of national politics and culture. This article aims to analyze the integral relationship between education and local culture as a national identity. Efforts to achieve this goal can be done through the formulation of a naming policy for the Batak people in local government education in North Sumatra Province. This research is important to be carried out in order to build political and cultural resilience, because based on the findings, it shows that local cultural identity is still relevant to the development of government politics to be integrated through local education. The research method uses a qualitative approach with a descriptive explanation. The data collection technique in this study was carried out using the purposive sampling technique. Data collection was carried out primarily through in-depth interviews, and supplemented with secondary data from scientific journals, books, and online news, including from the General Election Commission page which provides data on the names of North Sumatrans. The results of this study indicate that the conservation of the Batak people's personal names can be done by integrating local content education policies, namely through regional language lessons. This research can be said as something new, by uniting political and cultural approaches through an integrated education system. This research is expected to be of concern to academics, other researchers, and the government in reviewing education policies to integrate local wisdom as an effort to preserve national identity.